2013
DOI: 10.6000/2292-2598.2013.01.01.5
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Management of Aggression in Adults with Intellectual Disability

Abstract: Introduction: Aggression is a common behavioral problem seen in patients with intellectual disabilities (ID). The safety and efficacy of second generation antipsychotics (SGAs), mood stabilizers and antidepressants in the management of aggression in these individuals have minimally been studied. This review aims to 1) summarize the studies conducted using second generation antipsychotics, mood stabilizers and antidepressants in treating aggressive behaviors in patient with ID and 2) determine based on the exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Strategies to avoid side effects include the discontinuation of treatment in case of severe reactions, dose reduction, substitution by other psychoactive drug, or association of muscarinic anticholinergics (for example, biperiden). Risperidone is usually the first drug of choice especially in children and adolescents with ID, though scientific evidence is limited to a few studies: double-blind placebo-controlled cross-over trial with 27 patients, 21,22,9 another study including 8 patients with MR, 21 and an open-label fashion study with 11 male outpatients with autism and MR. 23…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Strategies to avoid side effects include the discontinuation of treatment in case of severe reactions, dose reduction, substitution by other psychoactive drug, or association of muscarinic anticholinergics (for example, biperiden). Risperidone is usually the first drug of choice especially in children and adolescents with ID, though scientific evidence is limited to a few studies: double-blind placebo-controlled cross-over trial with 27 patients, 21,22,9 another study including 8 patients with MR, 21 and an open-label fashion study with 11 male outpatients with autism and MR. 23…”
Section: Resultsmentioning
confidence: 99%
“…Carbamazepine in a double blind placebo-controlled cross-over study showed 40% improvement in overactivity; however, those also had elevated mood prior to treatment. 22…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations